Reka Cıpta Mesın Sortır Warna Benda Menggunakan Kamera PIXY2 CMUCAM5 - Sukma Meganova Effendi; Agatha Mahardika Anugrayuning Jiwatami; Nugroho Budi Wicaksono (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
Learning instrument is an important things in the learning process. Mechatronics systems that have complex circuits and controllers are not easily understood by Level 1 and 2 Students. This research applies the R&D method of Sugiyono to produce sorting machines that are easy to use and learn. The Pixy2 CMUcam5 camera is used for color detection. The controller circuit are used is Karnaugh Map circuit using Digital IC (NOT-AND-OR) and Arduino Uno. The color combinations processed in Karnaugh Map controller circuit are sorting 1 color (Red-R/ Green-G/ Blue-B), 2 colors (R&G/ R&B/ G&B), and 3 colors (R&G&B). Results of this sorting machine are can be operated easily, reprogrammed for both object color detection and DC motor & servo motor control, and rebuilt for the Karnaugh Map series. Validation of this study resulted in improvements to the initial turntable design which was improved with a timing belt mechanism to stabilize the turntable rotation. Lighting of indoor/outdoor does not affect the system because the Pixy2 has an internal LED so that the color is detected properly. The results of sorting with the final turntable design have good performance with an average success of 97.96% and a standard error of 0.58.